Studi Pustaka Kemampuan Menganalisis pada Pembelajaran Geometri dengan Menerapkan Teori Van Hiele terhadap Peserta Didik Kelas V SD - Amelia, Pricilla Bertha; Anugrahana, Andri (Jurnal Ilmu Pendidikan dan Sosial, 2024)
This study aims to determine the ability to analyze students on geometry learning by applying Van Hiele's theory to elementary theory to grade V elementary school students. The background of this researchis the author found an indication of the low ability to analyze learners in elementary school. This article aims to provide a proposal for Van Hiele Theory in geomtery learning. The method of this research is through literature study, which is collecting data from various books, articles, and research results to obtain the information being researched. research results to obtain information that is being researched. The approach used in this research is qualitative, which is to collect descriptive data from previous research as a source of research. as a source of research. The data that has been obtained is analyzed and concluded so as to get conclusions from several previous studies to answer how to provide proposals for the ability to analyze students through Van Hiele's theory in learning geometry. The results of the literature study This literature study shows that Van Hiele's theory has an important role in helping the teachers to develop learning methods that are suitable for geometry material, by going through the stages of geometry learning based on through the stages of learning geometry based on Van Hiele's theory, namely: 1) Recognition stage; 2) Analysis stage; 3) Deduction stage; 4) The accuracy stage. With this it can be concluded that Van Hiele's theory can help students and teachers in the process of learning geometry by going through the stages that have been proposed by Van Hiele stages that have been put forward by Van Hiele. In this case, the teacher can apply Van Hiele's theory to students starting from the introduction stage by using concrete media that is commonly found in the classroom. Introduction stage by using concrete media that is commonly found around, up to the analysis stage, namely the around, up to the analysis stage, which is the stage of students to analyze in depth about the observed flat shapes.